MJM MedTalks (S02E06): From Fractures to Fulfillment: Larry Funnell's Journey in Patient Engagement - Khiran Arumugam; Vanessa Ross; Larry Funnell; Katherine Lan; Samy Amghar; Renée-Claude Bider; Masha Samuel; Esther SH Kang; Jan Pack; Susan Joanne Wang (McGill Journal of Medicine)
McGill Journal of Medicine (MJM) MedTalks is a podcast series where members of the medical and health science communities from McGill and beyond are interviewed on topics related to career, research, advocacy, and more. The aim of MedTalks is to create a space where experienced professionals and researchers share information and advice for trainees in healthcare and medical sciences. In this episode, McGill medical student and MJM Podcast member Vanessa Ross, alongside McGill MSc graduate Khiran Arumugam interview Larry Funnell, a dedicated advocate for osteoporosis awareness and patient engagement. Larry shares his personal journey from his unexpected diagnosis of osteoporosis to becoming a leading patient partner in research and advocacy, particularly for men with osteoporosis. This discussion explores the value of patient engagement, strategies for involving men in osteoporosis initiatives, Larry’s contributions to the 2023 Osteoporosis Canada guidelines, and his advice for trainees in healthcare. The show notes include a glossary of terms, links to resources discussed in the episode, and a full transcript of the conversation.